Dar Czesława Miłosza w kontekście filozofii daru Jacques’a Derridy - Umerle, Tomasz (Przestrzenie Teorii, 2011)
The aim of this text is to present an attempt at the deconstructionist interpretation of Czesław Miłosz’s verse ‘Dar’ (‘Gift’). On the one hand, this paper emphasizes the moment of ‘dissemination’ of the literary work – the space between the title and ‘the rest’ of the text (which appeals more to the American deconstructionism) is seen as both a connection and an irreducible gap. On the other hand, this ‘dissemination’ is understood in terms offered by J. Derrida’s philosophy of gift. Miłosz used a word ‘gift’ in the title, but in the ‘textual corpus’ he made this donation ‘imperceptible’. This observation enables the Author to interpret Miłosz’s poem in the context of Derrida’s discourse of (im)possibility of gift. Consequently the title will be understood here as a gift to the text (the gift of meaning to the experience described there), but at the same time this gift/title will be seen as irreducibly separated from the ‘rest’ of the text, because of the relation between the title and the ‘textual corpus’.